1996
DOI: 10.1002/j.1460-2075.1996.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper-dependent degradation of the Saccharomyces cerevisiae plasma membrane copper transporter Ctr1p in the apparent absence of endocytosis.

Abstract: The cell surface protein repertoire needs to be regulated in response to changes in the extracellular environment. In this study, we investigate protein turnover of the Saccharomyces cerevisiae plasma membrane copper transporter Ctr1p, in response to a change in extra‐cellular copper levels. As Ctr1p mediates high affinity uptake of copper into the cell, modulation of its expression is expected to be involved in copper homeostasis. We demonstrate that Ctr1p is a stable protein when cells are grown in low conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(185 citation statements)
references
References 55 publications
10
171
4
Order By: Relevance
“…2A). However, we cannot rule out that the HA epitope tag alters putative COPT1 posttranslational regulatory mechanisms, including Cu-induced endocytosis, degradation, and transport blockage, which have been previously described for other eukaryotic high-affinity Cu transporters of the CTR family (Ooi et al, 1996;Petris et al, 2003;Guo et al, 2004;Liu et al, 2007). In this sense, although the Cys residues at the yeast Ctr1 C terminus are dispensable for Cu transport, they have been postulated to serve as Cu sensors and to play a crucial role in preventing Cu uptake when intracellular Cu levels rise (Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…2A). However, we cannot rule out that the HA epitope tag alters putative COPT1 posttranslational regulatory mechanisms, including Cu-induced endocytosis, degradation, and transport blockage, which have been previously described for other eukaryotic high-affinity Cu transporters of the CTR family (Ooi et al, 1996;Petris et al, 2003;Guo et al, 2004;Liu et al, 2007). In this sense, although the Cys residues at the yeast Ctr1 C terminus are dispensable for Cu transport, they have been postulated to serve as Cu sensors and to play a crucial role in preventing Cu uptake when intracellular Cu levels rise (Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, we still found it intriguing that hCTR1 and Arabidopsis COPT1, two proteins from two evolutionarily distant organisms, both function very well in yeast despite a complete lack of the region homologous to the carboxyl terminus of CTR1. This region has recently been shown to be involved in endocytosis of CTR1 in the presence of excess copper (33). The same authors showed that neither endocytosis nor the bulk of the region is necessary for copper transportation.…”
Section: Discussionmentioning
confidence: 98%
“…Cell pellets were collected by a 30-s centrifugation at 8,000 ϫ g and quickly placed in liquid nitrogen. Cell extracts were then made by standard alkaline lysis and trichloroacetic acid (TCA) precipitation procedures with some modifications (26). Briefly, 2.7 ϫ 10 7 cells were resuspended in 500 l of cold double-distilled water (ddH 2 O).…”
Section: Methodsmentioning
confidence: 99%